Stakeholders’ Perceptions of Agronomic Iodine Biofortification: A SWOT-AHP Analysis in Northern Uganda - Olum, Solomon; Okello, Collins; Odongo, Walter; Ongeng, Duncan; Steur, Hans De (Nutrients, 2018)
Agronomic biofortification (i.e., the application of fertilizer to elevate micronutrient concentrations in staple crops) is a recent strategy recommended for controlling Iodine Deficiency Disorders (IDDs). However, its success inevitably depends on stakeholders’ appreciation and acceptance of it. By taking Northern Uganda as a case, this study aimed to capture and compare the perceptions of seven key stakeholder groups with respect to agronomic iodine biofortification. Therefore, we employed a SWOT (Strength, Weaknesses, Opportunities & Threats) analysis in combination with an Analytical Hierarchy Process (AHP). Findings show that stakeholders (n = 56) are generally positive about agronomic iodine biofortification in Uganda, as its strengths and opportunities outweighed weaknesses and threats. Cultural acceptance and effectiveness are considered the most important strengths while the high IDD prevalence rate and the availability of iodine deficient soils are key opportunities for further developing agronomic iodine biofortification. Environmental concerns about synthetic fertilizers as well as the time needed to supply iodine were considered crucial weaknesses. The limited use of fertilizer in Uganda was the main threat. While this study provides insight into important issues and priorities for iodine biofortification technology in Uganda, including differences in stakeholder views, the application of the SWOT-AHP method will guide future researchers and health planners conducting stakeholder analysis in similar domains.